Design and Development of Electronic Tree Surveillance System for Detection of Illegal Wood Cutting - Kumar, J. Sai Praveen (My University, 2016)
Unauthorized cutting of trees is a prevailing global socio-economic problem. In the past few years, number of cases of illegally felled trees has been reported nationally and globally. Encroachments and illegal wood smuggling has resulted in severe downfall of Indian as well as global economy. Despite implementation and enforcements of various legislatory and regulatory measures, globally, this is still an existing problem. It is necessary to curb illegal exploitation of precious plantations and an objective oriented research can provide a robust and effective solution. Current research work ‘Electronic Tree Surveillance System’ is a new initiative for developing an effective, robust and simple approach to detect and classify malicious logging activity. ‘Electronic Tree Surveillance System’ (ETS System) is a multi-disciplinary project designed to provide a feasible and reliable model for eradication of illegal wood logging by strictly considering all the hardware development constraints like low cost components, effective, robust, easy availability of components, easy replicability of components, cheap installation and maintenance costs throughout the design and development of the system. Also, prototype system is developed to be reliable, realizable and feasible as per the existing scenario. An effective combination of fields like sensor technology and wireless sensor networks etc. are implemented and several signal processing approaches namely thresholding approach and machine learning approach have been implemented which can provide a solution for current problem. ETS system majorly operates on the tree vibrations considering a fact that forced vibrations are imparted on the tree trunk during a wood cutting process. Various traditional wood cutting techniques like axe cutting, handsaw cutting and machine cutting are employed and the research study was conducted on the trees existed in the university campus. This system consists of accelerometer sensory nodes for event identification and whenever there is an unauthorised or malicious activity identified, an alert will be generated at the Local Control Station (LCS) through the proposed system network. In a nutshell, a working prototype of feasible and realizable ‘Electronic Tree Surveillance System’ is designed and developed for eradication of illegal wood cutting by considering all possible parameters. This research has a huge social and economic impact and will provide the roadmap for further research work.
Master of Engineering -EIC
Keywords: Electronic Tree Surveillance; Illegal Wood Cutting; Accelerometers; activity recognition